Matching employment opportunities and expectations : a programme of action for Ceylon - International Labour Office (Geneva : International Labour Office, 1971)
"Matching Employment Opportunities and Expectations" analyzes many aspects of Ceylon's society, polity and economy with unemployment as its central focus. Prepared under the chairmanship of Professor Dudley Seers of Sussex University as part of the ILO's series on the World Employment Programme, it represents a multi-disciplinary effort to assist in designing a grand strategy for overcoming this urgent and growing problem so vividly dramatized by the youth rebellion of April 1971, which occurred while the mission was in Ceylon. The study examines the working of the labor market as a whole, a work force growing more rapidly than job openings, and an educational pattern which expands the number of white collar job candidates at a rate of 10 percent a year with little of the structural change in the economy necessary to absorb them.
The Report of an inter-agency team organized by the International Labour Office.
Includes bibliographical references.
rpm 16/04/2018
Ref
Keywords: Manpower policy; Unemployed